COVID-19 vaccine-induced immunity: Head-to-head comparison of mRNA (BNT162b2) versus inactivated (CoronaVac) vaccines - Kagina, Benjamin M.; Dochez, Carine (Respirology, 2022)
The public health benefits of vaccination are unequivocal: eradication of smallpox; near eradication of polio; elimination of maternal and neonatal tetanus; and control of several vaccine‐preventable diseases. Emergence of infectious diseases such as SARS‐CoV‐2 has demanded development of new vaccines. From December 2019 onwards, scientists were joined by diverse stakeholders to develop and deploy safe as well as effective COVID‐19 vaccines. By joining human and financial resources, the development of COVID‐19 vaccines was done at an unprecedented speed without compromising quality, safety and efficacy. The availability and widespread use of different COVID‐19 vaccines have prompted scientists to conduct comparisons on their effectiveness.
Keywords: inactivated; mRNA; vaccine‐induced immunity